the range is given in this way: y1=-1 y(n+1)=1/3y(n)+3 Find a f function y(n)=f(n) thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by blertta the range is given in this way: y1=-1 y(n+1)=1/3y(n)+3 Find a f function y(n)=f(n) thanks For for let so the difference equation becomes and choosing gives Seeking a solution of this in the form gives , thus giving the solution Now use your initial condition to find c. Note. If the difference equation is , it's harder problem.
View Tag Cloud